(untitled) (Economic and Political Thought, 2012)
The article is a critical, in-depth analysis based on the author’s experience, which shows that apart from money and motivation, cooperation of higher education and science with industry is necessary for the development of innovation processes in every country. In order to achieve this objective, universities must open up to the surrounding and undertake cooperation with industry. The author calls for the creation of senates or university boards that would be composed of an adequate proportion of representatives of industry and public life and could play the role of boards of trustees, which exist in other countries.